Mutational analysis of Escherichia coli DNA ligase identifies amino acids required for nick-ligation in vitro and for in vivo complementation of the growth of yeast cells deleted for CDC9 and LIG4. - Sriskanda, V (1999)
We report that the NAD-dependent Escherichia coli DNA ligase can support the growth of Saccharomyces cerevisiae strains deleted singly for CDC9 or doubly for CDC9 plus LIG4. Alanine-scanning mutagenesis of E.coli DNA ligase led to the identification of seven amino acids (Lys115, Asp117, Asp285, Lys314, Cys408, Cys411 and Cys432) that are essential for nick-joining in vitro and for in vivo complementation in yeast. The K314A mutation uniquely resulted in accumulation of the DNA-adenylate intermediate. Alanine substitutions at five other positions (Glu113, Tyr225, Gln318, Glu319 and Cys426) did not affect in vivo complementation and had either no effect or only a modest effect on nick-joining in vitro. The E113A and Y225A mutations increased the apparent K (m)for NAD (to 45 and 76 microM, respectively) over that of the wild-type E. coli ligase (3 microM). These results are discussed in light of available structural data on the adenylylation domains of ATP- and NAD-dependent ligases. We observed that yeast cells containing only the 298-amino acid Chlorella virus DNA ligase (a 'minimal' eukaryotic ATP-dependent ligase consisting only of the catalytic core domain) are relatively proficient in the repair of DNA damage induced by UV irradiation or treatment with MMS, whereas cells containing only E.coli ligase are defective in DNA repair. This suggests that the structural domains unique to yeast Cdc9p are not essential for mitotic growth, but may facilitate DNA repair.